Platero and I - Jiménez, Juan Ramón, 1881-1958 (Aris & Phillips Hispanic classics., 2011)
Juan Ramon Jimenez, 1956 winner of the Nobel Prize, published Platero and I in 1914. Like Le Petit Prince by Antoine de Saint-Exupery and Lewis Carroll's Alice in Wonderland, Platero and I is a book not only for children, but for adults as well. It is an allegory of the deepest human emotions. As with Don Quixote, in the Spanish golden Age, Platero and I has become the classic of 20th century Spain. Known as the 'Andalucian elegy', it follows the journey of the author and his donkey Platero through the countryside of Moguer, birthplace of Juan Ramon Jimenez. In his review of this translation, John Dixon wrote: 'This translation reflects the spirit of the work as poetry, however, in the attention to detail and in the understanding that in such detail, in the individual words and the network of relations in which they are placed, lies the ability to capture the rhythmic harmonies of the original. If the often repeated debate as to the translatability or untranslatability of poetry has to be answered, then this translation, in every way comparable to a translation of poetry as far as approach is concerned, testifies to the fact that it can be done'. In her preface to this translation, Susan Bassnett writes: 'this translation is proof that an intrinsically Spanish book can be made accessible to readers from other cultural traditions'. Salvador Ortiz-Carboneres was brought up in the Valencian countryside, which helped him to understand the idyllic background in which Platero and I is set.